Open to Disruption : Time and Craft in the Practice of Slow Sociology - Nelson, Margaret K., 1944-; Hertz, Rosanna; Garey, Anita Ilta, 1947- (Book collections on Project MUSE., 2014)
"The noted scholars in this collection expose the backstage stories about surprises that disrupted the smooth trajectory of their research. With both dignity and beauty, the collection as a whole evokes the risks, uncertainty, and excitement of innovative social science research"--